Pregnancy diagnosis in pigs using seed germination inhibition test: An evaluation study in Meghalaya - KUMAR, ASHOK; DEWRY, R K; SINGH, RAM; JAT, P C; SINGH, MAHAK; KADIRVEL, G (The Indian Journal of Animal Sciences, 2017)
The present study was carried out on 315 breedable sows of approximately 2-4 years of age irrespective of parity with good body condition in varying managemental conditions under subtropical rainfall areas of Meghalaya. These animals were fed on kitchen wastes with locally available green fodder. The animals those were non return after one month (range 28-34 days) post-breeding, were grouped as positive group (n=215), non-mated pigs as negative group (n=100) and distilled water as control group (n=100). Urine samples were collected in clean, sterilized plastic containers through manual method at farmer’s door during natural micturition in the morning and diluted at the ratio of 1:4 with distilled water for pregnancy diagnosis on the same day of collection. Wheat seed with average 85% of germination after 48 h at room temperature was selected for the entire study. In each sterile petri dish, 15 wheat seeds were taken on the blotting paper and 15 ml of diluted urine was added and covered with trays to avoid evaporation, and kept undisturbed for 48 h at room temperature. Test was conducted in triplicate for each animal. Control test was also carried out with the addition of distilled water only to the wheat seeds. The germination inhibition percentage and shoot length (cm) of germinated seeds in each petri dish was recorded and calculated at 48, 72 and 96 h after adding the sample. All data were analysed using two-way ANOVA by SPSS software and expressed as Mean±SE. The mean germination inhibition percentage of wheat seeds was significantly different between pregnant (75.66±3.48), non-pregnant (28.70±2.96) and control (19.48±2.69) groups. Shoot length (cm) was significantly less in pregnant group when compared to non pregnant and control groups, and also significantly different within the group at different time intervals. Mean germination inhibition percentage and reduced shoot length in positive group was indicative of pregnancy status. Hence, it can be concluded that seed germination inhibition is a useful technique to detect pregnancy in pigs as a simple, non-invasive and cost effective method, and must be popularized among the farmers, veterinary officers and paraveterinary workers for field level application.